ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TAHU TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DESA CURAH JERU KABUPATEN SITUBONDO - Kumala Sari, Reza Dwi; Mujianti , Sri Ayudha; Munawwir, Zainul (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of price and product quality on consumer purchasing decisions at the Tofu Factory of Ibu Watik in Curah Jeru Village, Situbondo Regency. The research method used is quantitative with a descriptive approach. Data collection techniques included observation, questionnaires, and documentation. The sample consisted of 100 respondents who are end consumers. The analysis results show that both price and product quality, individually and simultaneously, have a significant effect on purchasing decisions. This confirms that consumers take into account affordable prices and good product quality when making purchasing decisions. These findings are expected to provide strategic input for local businesses to improve their product competitiveness.